2019
DOI: 10.1039/c8bm01188e
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular crowding tunes 3D collagen architecture and cell morphogenesis

Abstract: Macromolecular crowding of collagen I during polymerization produces short, degradation-resistant fibrils that induce collective morphogenesis of breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 82 publications
(101 reference statements)
1
46
0
Order By: Relevance
“…[ 274 ] The crowding effect produces tighter fibril networks and decreases susceptibility of proteinase‐mediated degradation, without significantly altering matrix stiffness. [ 275 ] A novel bioprinting strategy has been implemented to tune the degree of MMC within each printed region to create 3D bioprinted hierarchical porous collagen‐based constructs [ 268 ] ( Figure 7 ). The use of macromolecules manipulates the collagen fibrillogenesis process by exerting an excluded volume effect on the surrounding collagen molecules; an increasing macromolecule concentration results in the formation of larger pores and increased porosity within the 3D collagen matrices.…”
Section: Potentialsmentioning
confidence: 99%
“…[ 274 ] The crowding effect produces tighter fibril networks and decreases susceptibility of proteinase‐mediated degradation, without significantly altering matrix stiffness. [ 275 ] A novel bioprinting strategy has been implemented to tune the degree of MMC within each printed region to create 3D bioprinted hierarchical porous collagen‐based constructs [ 268 ] ( Figure 7 ). The use of macromolecules manipulates the collagen fibrillogenesis process by exerting an excluded volume effect on the surrounding collagen molecules; an increasing macromolecule concentration results in the formation of larger pores and increased porosity within the 3D collagen matrices.…”
Section: Potentialsmentioning
confidence: 99%
“…Gels were polymerized at 37°C in a humidified incubator. To modify the structure of the collagen fibers to obtain LDSF gels we used a technique previously reported by our group [11]. Briefly, Polyethylene glycol (PEG, MW = 8000, Sigma, St. Louis, MO) was solubilized in phosphate-buffered solution (PBS) and filter sterilized.…”
Section: D Culture In Collagen I Matrixmentioning
confidence: 99%
“…To study the influence of matrix architecture on cancer cell migration, we used a previously developed method to tuned collagen fibril organization independently of altering density and stiffness by molecular crowding with polyethylene glycol (PEG) during polymerization and cell embedding [9,11]. PEG, an inert crowding agent, was subsequently washed out of the polymerized matrix.…”
Section: D Collagen Architecture Is Tuned By Molecular Crowdingmentioning
confidence: 99%
“…Another interesting observation is, that the ECM produced by adult fibroblasts under MMC conditions is able to propagate human embryonic stem cells, even outperforming Matrigel ( 19 ). With respect to natural biomaterials, it was found that MMC not only enhances the polymerization rate of collagen type I, but also tunes fiber diameter and organization, a fact that can be explored for optimizing the properties of soft collagen hydrogels ( 20 23 ) or collagen films (planar constructs) ( 24 , 25 ). Lastly, MMC has also been used for improving hydrogels derived from decellularized matrices ( 26 ).…”
Section: Introductionmentioning
confidence: 99%